Screening and target identification of bioactive compounds that modulate cell migration and autophagy. Issue 15 (1st August 2016) - Tashiro, Etsu; Imoto, Masaya
Graphical abstract: Abstract: Cell migration is a fundamental step for embryonic development, wound repair, immune responses, and tumor cell invasion and metastasis. It is well known that protrusive structures, namely filopodia and lamellipodia, can be observed at the leading edge of migrating cells. The formation of these structures is necessary for cell migration; however, the molecular mechanisms behind the formation of these structures remain largely unclear. Therefore, bioactive compounds that modulate protrusive structures are extremely powerful tools for studying the mechanisms behind the formation of these structures and subsequent cell migration. Therefore, we have screened for bioactive compounds that inhibit the formation of filopodia, lamellipodia, or cell migration from natural products, and attempted to identify the target molecules of our isolated compounds. Additionally, autophagy is a bulk, non-specific protein degradation system that is involved in the pathogenesis of cancer and neurodegenerative disorders. Recent extensive studies have revealed the molecular mechanisms of autophagy, however, they also remain largely unclear. Thus, we also have screened for bioactive compounds that modulate autophagy, and identified the target molecules. In the present article, we introduce the phenotypic screening system and target identification of four bioactive compounds.